The Relationship between Knowledge Level of Handlers and Contamination of Escherichia coli and Coliform Bacteria at Refill Drinking Water Depots in Air Putih Subdistrict - Simanjuntak, Risyhal Ramadhani; Kurniawan, Deny; Pramaningsih, Vita (HIGIENE: Jurnal Kesehatan Lingkungan, 2025)
The aim of this research is to determine whether there is a relationship between the level of knowledge of refill drinking water depot handlers (DAMIU) and the contamination of Escherichia coli bacteria and coliform bacteria found in Air Putih Village, Samarinda City. To analyze water samples from 14 DAMIUs, 9 of which did not have appropriate certificates, and 5 others had appropriate certificates, a laboratory experimental method with a quantitative approach with a cross-sectional design was used. There was an almost significant relationship (p=0.078) between the level of knowledge of handlers and contamination with Escherichia coli and coliform bacteria. The results of data analysis using the chi-square test are shown. The research results show that increasing knowledge is the key to influencing the quality of refillable drinking water. This research found that residents in Air Putih Subdistrict, Samarinda City have a high level of knowledge about handling.